The accident at Chernobyl and outcome of pregnancy in Finland - Harjulehto, T.; Aro, T.; Rita, H.; Rytömaa, T.; Saxén, L. (BMJ, 1989)
OBJECTIVE--To evaluate the outcome of pregnancy in Finnish women after the accident at the Chernobyl nuclear power plant on 26 April 1986. DESIGN--Geographic and temporal cohort study. SETTING--Finland divided into three zones according to amount of radioactive fallout. SUBJECTS--All children who were exposed to radiation during their fetal development. Children born before any effects of the accident could be postulated--that is, between 1 January 1984 and 30 June 1986--served as controls. INTERVENTIONS--Children were divided into three temporal groups: controls, children who were expected to be born in August to December 1986, and children who were expected to be born in February to December 1987. They were also divided, separately, into three groups according to the three geographic zones. END POINT--Incidence of congenital malformations, preterm births, and perinatal deaths. MEASUREMENTS AND MAIN RESULTS--There were no significant differences in the incidence of malformations or perinatal deaths among the three temporal and three geographic groups. A significant increase in preterm births occurred among children who were exposed to radiation during the first trimester whose mothers lived in zones 2 and 3, where the external dose rate and estimated surface activity of caesium-137 were highest. CONCLUSIONS--The results suggest that the amount of radioactive fallout that Finnish people were exposed to after the accident at Chernobyl was not high enough to cause fetal damage in children born at term. The higher incidence of premature births among malformed children in the most heavily polluted areas, however, remains unexplained.